School-Student Relations: a changing history - Miriam Waidenfeld Chaves (Universidade Federal do Rio Grande do Sul, 2015)
During the last century, whilst school was turned into the socializing agent par excellence, it became an object of dissatisfaction, indicating that it should now be seen under this double movement: historically, we are faced with the consolidation of the school form of socializing and, at the same time, we witness the demise of its institutional program. The present text puts forward, under a sociohistorical approach, some considerations about the establishment of the school paradigm in modernity, and analyzes the school crisis, highlighting the hegemonic and shifting character of certain manners of thinking, acting and feeling within one of the main social groups that comprise it: the pupils.